The Worldview Concept and Aldo Leopold’s Project of ‘World View’ Remediation - Callicott, J. Baird 1941- (2011)
A Sand County Almanac has a single overarching theme and purpose—worldview remediation: to replace the biblical with an evolutionary-ecological worldview. The epistemological foundations of the worldview concept were established by Kant, who rendered ‘reality’ phenomenal and potentially plural. No worldview is true, but competing worldviews may be adjudicated by the application of three criteria of tenability: (1) self-consistency; (2) consistency with and comprehensive of all phenomenal experience; (3) aesthetical and spiritual satisfaction. A Sand County Almanac’s ‘Marshland Elegy’ and ‘On a Monument to the Pigeon’ explore the aesthetic and spiritual potentiality of the theory of evolution. ‘Odyssey’, ‘Thinking Like a Mountain’, and ‘Song of the Gavilan’ explore the aesthetic and spiritual potentiality of ecology. ‘The Land Ethic’ explores the axiological and normative implication of the evolutionary-ecological worldview. Subsequent changes in ecology problematize the summary moral maxim of ‘The Land Ethic’. Worldview remediation is now more challenging, but also more necessary than ever.
Keywords: Aldo Leopold; Axiology; Kant; White; Ecology; Epistemology; Evolution